Tubular end-capped electrodeposited CdSe nanofibers: Enhanced photochemistry - Min, SK; Joo, OS; Jung, KD; Mane, RS; Han, SH (ELSEVIER SCIENCE INC, 2006)
Here, we report for the first time tubular end-capped nanofibers of CdSe on ITO substrates that have been developed using electrodeposition chemistry. We investigated the surface morphology and extended further to examine photoelectrochemical performance. As-formed ITO/CdSe/polysulphide/Pt photoelectrochemical cell showed 2% photo-conversion efficiency under 80 mW/cm(2) light intensity, when Used in the photoelectrochemical-type cells. (c) 2005 Elsevier B.V. All rights reserved.